Passaggio a Sud-Ovest. Itinerario di miniera nella Sardegna sud-occidentale - Francesca Sanna (Diacronie. Studi di Storia Contemporanea, 2015)
Sulcis-Iglesiente, in the south-west of Sardinia, is a region with an historical experience of mining industry. During an entire century, this activity left some documents and material tracks, now transformed in ruins. The purpose of this article is to create an itinerary with photos and real geographic references in order to discover and explain the history told by these remains. With ancient contributes written by travellers of the past and historical images of the region, this voyage in sardinian mining world reflects also the heritage left on the area and the population.